STRATEGI READING RECORD DALAM MEMBANGUN MINAT BACA SISWA DI SD LUQMAN AL HAKIM SURABAYA - PUPUT MELATI, ISMI; SHOLEH, MUHAMAD (Inspirasi Manajemen Pendidikan, 2019)
Abstract: The purpose about this research to describe and analyze about (1) librarian strategies in developing reading interest of students at SD Luqman Al Hakim Surabaya; (2) Teachers strategy in developing students interest in reading at SD Luqman Al Hakim Surabaya. This study uses a qualitative approach with a case study method. Data retrieval uses interview, observation, and documentation study techniques. Analysis of the data used is data condensation, data presentation, and data verification. The validity test of the data is done using data source triangulation, technical triangulation, and member check. Check the data wetness using credibility test, transferability test, dependability test and confirmability test. The stages of research conducted by researchers are (1) Preparation stage; (2) Implementation phase; and (3) Report preparation phase.The results of the study can be explained as follows: (1) The strategy of librarians namely librarians has a superior program and supports in developing students reading interest, the program is a reading record program. The reading record program is a monitoring book for the achievement of reading books by students in the lower classes which is useful for encouraging students to love reading. In addition to the reading record program, librarians also have library services, namely circulation services and audio visual services. (2) The teachers strategy is that the teacher as homeroom teacher participates in carrying out the reading record in the learning process. In addition, the teacher also monitors students to find out the development of their students, especially the development of students in reading books. Keywords : Reading record strategy, Library Program, reading interest. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis tentang (1) strategi pustakawan dalam membangun minat baca siswa di SD Luqman Al Hakim Surabaya; (2) Strategi guru dalam membangun minat baca siswa di SD Luqman Al Hakim Surabaya. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Pengambilan data menggunakan teknik wawancara, observasi, dan studi dokumentasi. Analisis data yang digunakan adalah kondensasi data, penyajian data, dan verifikasi data. Uji keabsahan data dilakukan dengan menggunakan triangulasi sumber data, triangulasi teknik, dan membercheck. Pengecekan keabsahan data menggunakan uji kredibilitas, uji transferabilitas, uji dependabilitas dan uji konfirmabilitas. Tahap-tahap penelitian yang dilakukan peneliti adalah (1) Tahap persiapan; (2) Tahap pelaksanaan; dan (3) Tahap penyusunan laporan. Hasil penelitian dapat dijelaskan sebagai berikut: (1) Strategi pustakawan yaitu pustakawan mempunyai program yang unggul dan menunjang dalam membangun minat baca siswanya, program tersebut yaitu program reading record. Program reading record adalah buku monitoring pencapaian membaca buku oleh murid di kelas bawah yang berguna untuk mendorong siswa agar gemar membaca. Selain program reading record, pustakawan juga mempunyai layanan perpustakaan yaitu layanan sirkulasi dan layanan audio visual. (2) Strategi guru yaitu guru sebagai wali kelas turut serta melaksanakan reading record di dalam proses pembelajaran. Selain itu guru juga melakukan monitoring kepada siswanya untuk mengetahui perkembangan siswanya terutama perkembangan siswa dalam membaca buku. Kata Kunci: Strategi reading record, Program Perpustakaan, minat baca.